Wpływ kryzysu subprime na determinanty wariancji warunkowej indeksu WIG20 - Buszkowska-Khemissi, Eliza; Płuciennik, Piotr (Uniwersytet Ekonomiczny w Poznaniu, 2014)
The subprime crisis which started in USA in August 2007 and soon affected other countries also had an effect on the financial markets. It tiggered an intervision of the long standing upward trends and at the same time it generated increaing nervousness among investors while the market became more unpredictable. In the article we research the influence of implied, historic and realied volatility on the conditional variance of WIG20 index in two particular periods - preceding the financial crisis and during the subprome crisis.The reduction of these natural dependencies would mean an increase in the unpredictability of the market, which reacts more strongly to outside signals then expectations. We also try to indentify risk premium and leverage effects in both of the analysed periods.
Keywords: kryzys; determinanty; zmienności; EGARCH